SIKAP MASYARAKAT DUSUN PASIR LAUT TERHADAP KEBERADAAN HUTAN MANGROVE DI DUSUN PASIR LAUT KECAMATAN MEMPAWAH HILIR KABUPATEN MEMPAWAH - nutriawani, rafika; Nurdjali, Bachrun; Nugroho, Joko (JURNAL HUTAN LESTARI, 2017)
Mangrove forests have an important role in protecting the coastline, maintaining and balancing ecological balance estuary in coastal areas that receiving most of the pressure. Mangrove forest ecosystem has a variety of functions and benefits there are very important for other ecosystems. This is forests, water, and natural surroundings. The existence of mangrove also give effect to the community residing on the seashores, this study aimed to determine the attitudes of society in Dusun Pasir Laut to the existence of mangrove forest in Dusun Pasir Laut and analyze the relationship between the level of perception, knowledge and cosmopolitan attitude of society Dusun Pasir Laut against the existence of mangrove forest in Dusun Pasir Laut. The mangrove forest in Dusun Pasir Laut, Mempawah Hilir Subdistrict is one of the livelihoods of local people. Dusun Pasit Laut community in diverse activities to live. Judging from the level of education and socioeconomic levels are diverse, people in Dusun Pasir Laut, has diverse knowledge levels that can cause differences in attitude in view of the existence of a mangrove forest. Through institutions need to be developed to the community so as to play an active role in maintaining, protecting and developing mangrove ecosystem in the long term. Keywords: attitudes and perceptions, cosmopolitan, mangrove